Rice Leaf Folder (Cnaphalocrosis medinalis) Infestation at Different Planting System and Varieties - Saleh, Teddy Wahyana; Nur, Amin; Saragih, Ammini A. (Akta Agrosia, 2020)
The proliferation of pests is most influenced by the host (plants) and other environments including plant distance and humidity. Agriculture research and development departement has been released many varieties of rice but their resistance to pests and diseases on various developmental areas is different. The study aims to determine the population and attacks intensity of Rice Leaf Folder (Cnaphalocrosis medinalis) on farming rice  jajar legowo ganda and regular systems (tegel). The research has been carried out on farmers  fields in Buntulia Village, Duhiadaa District, Pohuwato Regency from June to October 2019. The study  used  a Split plot research design with four replications. The main plot is farming rice jajar legowo ganda  and  regular system. Sub plots are varieties: 1). Inpari 30, 2). Inpari 31, 3). Inpari 42, and 4). Situbagendit. Cnaphalocrosis Medinalis  was observed when the plants age 5, 7, 9, and 11 week after planting (WAP) on 30 clumps per plot. The results showed Cnaphalocrosis medinalis  attacking on all varieties in both systems. However, Cnaphalocrosis medinalis attacks on the farming rice jajar legowo ganda (average 7.96 %) has as lower as than regular system (av. 3.95 %)) on the observations per weeks. The intensity of Cnaphalocrosis medinalis attacks on Inpari 31 (av. 5.56 %)   as lower as than Situbagendit  (av. 13.43 %). The result showed highest populations Cnaphalocrosis medinalis was found on regular system (av. 9.35 h / c) lowest Cnaphalocrosis medinalis populations was on the rice farming jajar legowo ganda (av. 7.96 h / c).  Highest populations of  Cnaphalocrosis medinalis was found on Situbagendit variety and Inpari 30 variety has lowest populations. Cnaphalocrosis medinalis attack intensity, generally increasing with rice age, the population density was relatively decreased because control doing.Keywords: rice leaf folder, planting system, varieties.